Creativity of director’s solutions in Kyz-Zhibek play: colour, visual body movements, and their interaction - Tsoy, Anna; Urazymbetov, Damir (Creativity Studies, 2025)
The artistic creativity trends of the contemporary theatrical process are aimed at complicating forms, deepening meanings, expanding the space for creating a new theatrical form, and, as a result, searching of the creative solution to comprehend the results of such experiments. Since contemporary theaters are targeted at developing and creating new performances, it is necessary to understand the potential of visual drama in the context of equality and effectiveness of all stage visual elements. As a variant of the adequate language search for the theater and society communication, visual dramaturgy becomes one of the fundamental in the context of the contemporary Kazakh theater development. In this study, the authors set out to identify and analyze the colour and body movement in their interaction on the example of the Kazakh national play Kyz-Zhibek (Kazakh: Qyz Jybek) directed by Dina Zhumabayeva in 2020, as it is visual intertext and reminiscence, addressed to the viewer reflection. As a creative solution to the study of the colour and body movement relationship in the visual network of signs organization of the play Kyz-Zhibek, such methods as semiotic analysis, vectorization by Patrice Pavis and the method of visual dramaturgy by Knut Ove Arntzen were used. In the study, we followed the goal of clarifying how the director creates and fills colour with body movement, strengthening and expanding meanings, and how this process can be studied and analyzed in order to be used for communication with the audience and in further contemporary theater studies.